Prevalence of Congenital Heart Disease in Chinese Children With Different Birth Weights and Its Relationship to the Neonatal Birth Weight - Yan, Hui; Zhai, Bo; Feng, Ruiling; Wang, Penggao; Zhang, Yaodong; Wang, Yiran; Hou, Yuwei; Zhou, Yang (Frontiers in Pediatrics, 2022)
Objective This study aimed to examine the prevalence and the related risk factors of congenital heart disease (CHD) in children with different birth weights in China and the relationship between the subtypes of CHD and birth weight (BW). Methods This study conducted a cross-sectional survey on the data collected in the children’s congenital heart disease database (CHDD) established in China. This database contained data from one Grade A, Level III Children’s Public Hospital in Zhengzhou, Henan. The study included all the children and their parents in the database from 2014 to 2020 as the study subjects, and the missing data were processed by means of imputation. Diagnoses of CHD were coded using the International Classification of Diseases version 10 (ICD-10), and subtypes were classified by the codes Q20 to Q26. We reported the prevalence of CHD based on birth weight and gestational age and analyzed the related risk factors for children with CHD in different birth weight groups and factors for children of the same birth weight groups between the CHD groups and the non-CHD groups. The generalized linear model was used to assess the association between the subtypes of CHD and BW by establishing three adjusting models, and the data were stratified for further analysis by urban-rural and infant gender. Results A total of 42,814 children were identified as having CHD among 5,071,799 live children; the overall prevalence of CHD was 8.44 per 1,000 live births during 2014–2020; and the three subtypes with the highest prevalence of CHD were atrial septal defect (ASD) (2.75‰), ventricular septal defect (VSD) (2.57‰), and patent foramen ovale (PFO) (1.12‰). The prevalence of CHD was 18.87‰ in the group with BW <1,500 g, 12.84‰ in the group with BW 1,500–2,500 g, 8.24‰ in the group with BW 2,500–4,000 g, and 4.80‰ in the group with BW ≥4,000 g. The prevalence of CHD was 16.62‰ in the small for gestational age (SGA) group, 6.99‰ in the appropriate for gestational age (AGA) group, and 6.40‰ in the larger for gestational age (LGA) group. Parental factors such as drinking, smoking, viral infections, peri-pregnancy exposure to radioactive substances, low family monthly expenditure, and low Apgar scores at 1 and 5 min were related to the increased risk of CHD in the offspring. Parental supplementation of folic acid and exercise during the peri-pregnancy period could reduce the risk of CHD in the offspring. The results of Model 3 adjusting for confounding variables showed that infants with ASD had a birth weight 461 g lower (95% CI: −1,085, –128), infants with VSD had a birth weight 426 g lower (95% CI: –932, –120), infants with tetralogy of Fallot (TOF) had a birth weight 532 g lower (95% CI: –987, –168), and without classification, infants with CHD had a birth weight 973 g lower (95% CI: –1,502, –204). Conclusion In very low birth weight (VLBW) and low birth weight (LBW) infants, CHDs are more prevalent than in the general live-born population. Moreover, some peri-pregnancy factors of parents are closely related to the occurrence of CHD in offspring; different types of heart defects can lead to LBW. Therefore, if the fetus is found to have a heart defect during the prenatal examination, the mother should pay more attention to maintaining weight and ensuring that the fetus is within the normal weight range, thereby increasing the postpartum survival rate, reducing complications, and promoting children’s health.